The Influence of Digital Mediation of Financial Literacy on Fashion Trend Social Circulation and Lifestyle Behavior of Millennials in Sorong Regency - Aryfudin; Nurhidayah; M. Ridwan Basalamah (LP2M IAIN Palopo, 2025)
This study aims to determine the influence of Fashion Trend Association on the Lifestyle Behavior of the Millennial Generation through Digital Financial Literacy as a mediating variable in the Millennial Generation in Sorong Regency. This study was conducted on 65 Millennial Generations. using nonprobability sampling techniques, namely not providing equal opportunities or chances for each element. Data analysis techniques using Smart PLS (Partial Least Square) Software. The results of the quantitative analysis in this study indicate that the Millennial Generation of Sorong Regency perceives all research, namely Fashion Trend Association, Digital Financial Literacy and Millennial Generation Lifestyle Behavior. The results of the study show that Fashion Trend Socialization has a Positive and Significant Influence on the Lifestyle Behavior of the Millennial Generation in Sorong Regency. Fashion Trend Socialization has a Positive and Significant Influence on the Digital Financial Literacy of the Millennial Generation and Fashion Trend Socialization has a Positive and Significant Influence on the Lifestyle Behavior of the Millennial Generation through Digital Financial Literacy for the millennial generation of Sorong Regency society. Digital Financial Literacy does not affect the lifestyle behavior of the Millennial Generation of Sorong Regency society